Modeling upper eyelid kinematics during spontaneous and reflex blinks - Malbouisson, Jorge Mario C.; Messias, Andre; Garcia, Denny Marcos; Cechetti, Sheila de Paula; Barbosa, Jose Carlos [UNESP]; Velasco Cruz, Antonio Augusto (Elsevier B.V., 2010)
To test a mathematical model for measuring blinking kinematics.Spontaneous and reflex blinks of 23 healthy subjects were recorded with two different temporal resolutions. A magnetic search coil was used to record 77 blinks sampled at 200 Hz and 2 kHz in 13 subjects. A video system with low temporal resolution (30 Hz) was employed to register 60 blinks of 10 other subjects. The experimental data points were fitted with a model that assumes that the upper eyelid movement can be divided into two parts: an impulsive accelerated motion followed by a damped harmonic oscillation.All spontaneous and reflex blinks, including those recorded with low resolution, were well fitted by the model with a median coefficient of determination of 0.990. No significant difference was observed when the parameters of the blinks were estimated with the under-damped or critically damped solutions of the harmonic oscillator. on the other hand, the over-damped solution was not applicable to fit any movement. There was good agreement between the model and numerical estimation of the amplitude but not of maximum velocity.Spontaneous and reflex blinks can be mathematically described as consisting of two different phases. The down-phase is mainly an accelerated movement followed by a short time that represents the initial part of the damped harmonic oscillation. The latter is entirely responsible for the up-phase of the movement. Depending on the instantaneous characteristics of each movement, the under-damped or critically damped oscillation is better suited to describe the second phase of the blink. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Blink; Harmonic oscillation; Mathematical model